2020
DOI: 10.24093/awej/vol11no1.14
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Use of Language in Islam-related News: Evidence from Selected Non-Western Online Newspapers

Abstract: The manner in which language is utilized in reporting Islam is disheartening. This is because sensationalized language, especially in the news media, could reinforce negative stereotypes. As such, those who rely on the media to understand Islam are likely to develop negative preconceptions about the religion. This study aims to investigate how the non-western online newspapers use language in news coverage of Islam. Content analysis was used to collect and analyze the data. Using purposive sampling, Punch and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In addition, words and phrases constitute part of texts which convey messages and ideas. In this regard, Hassan, et al (2020) argued that "the media's tendency to associate Islam with terrorism depends largely on the manner in which the news story is constructed" (p. 173). Reynolds (2015) found that negative words and phrases are significantly used in news coverage of Islam and Muslims.…”
Section: News Coverage Of Islam In the Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, words and phrases constitute part of texts which convey messages and ideas. In this regard, Hassan, et al (2020) argued that "the media's tendency to associate Islam with terrorism depends largely on the manner in which the news story is constructed" (p. 173). Reynolds (2015) found that negative words and phrases are significantly used in news coverage of Islam and Muslims.…”
Section: News Coverage Of Islam In the Mediamentioning
confidence: 99%
“…In any case, after the 9/11 attacks, the media paid much attention on Islam-related news with various coined terms such as "Islamic terrorism", "Islamic fanaticism", "Muslim extremists" (Mohideen & Mohideen, 2008;Nurullah, 2010;Ridouani, 2011). These kinds of terminologies constitute part of media texts with the tendency to associate Islam with terrorism depending largely on the manner in which the news story is constructed (Hassan, Azmi, & Abdullahi, 2020). As a result of the distortion of words' meaning, taking into consideration the news context, the media reinforce stereotypes and negative images of Islam (Moore et al, 2008;Reynolds, 2015;Hassan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%